PERAN PERSERIKATAN BANGSA-BANGSA DALAM MENANGANI PELANGGARAN HAK ASASI MANUSIA DI KOREA UTARA PERIODE 2015-2018 - Anisa Rizkyta, (2021)
This study aims to analyze the role of the United Nations (UN) in dealing with human rights violations in North Korea. This study uses qualititave research methods that are supported by theories and concept used to examine this research, namely the concept oh Human Rights, International Organization theory, and Functional theory in Internastional Organizations. The UN, through a special council formed to deal with humanitarian issues, namely the United Nations Human Rights Council (UNHRC) is slowly detecting crimes againts human rights in North Korea. As a further action, UNHRC established a commission devoted to dealing with human rights violation in North Korea called as the Commission of Inquiry (COI) and established a UN office in South Korea called the Human Rights Field Office based on the recommendations proposed in the COI report releasen in 2014. Human rights in North Korea, UNHRC carries out three processes; the first is the identification of human rights violations in North Korea, the second is the representation of UNHRC by establishing an office in South Korea and the activities carried out every year, the last is the efforts of UNHRC - South Korea by diplomatic means such as the ratification of the Human Rights Act in North Korea and the Pyongyang Declaration.